Selekcja kredytobiorców przeprowadzona za pomocą modelu probitowego jako funkcji klasyfikacji w drzewie decyzyjnym - Steuden, Michał (Probit model as the cart function in the process of borrowers' selection, 2006)
This article shows how to incorporate probit model into CART system in an aim to enable proper classification of potential borrowers. Probit systems are widely known but the problems they face is the level of accuracy and difficulties with treating categorical variables. Although there are techniques which incorporate such variables but at the same time the number of variables increases significantly and a covariance matrix can be difficult to estimate. Incorporation of a probit model into CART system enables to build system of probit equations with fewer explaining variables (at every split node) and with higher rate of accuracy at the same time. What is more important is that it inherits ability to predict default instances.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 509-515